Residue Levels of Organochlorine Pesticides in Breast Milk and Its Associations with Cord Blood Thyroid Hormones and the Offspring’s Neurodevelopment - Kao, Cheng-Chih (Int J Environ Res Public Health, 2019)
Previous studies have demonstrated that organochlorine pesticide (OCP) exposure has a negative impact on the neurological function of infants. Only a few reports have investigated the thyroid and growth hormones and their relationship to neurodevelopment after human exposure to OCPs, especially in the case of infants. Our goal was to determine whether breastmilk OCP residues were associated with negative impacts and/or alterations in the neurodevelopment of infants among specific southern Taiwanese mother–breastfed infant pairs. Our subjects (n = 55 pairs) were recruited from southern Taiwan between 2007 and 2010. The thyroid and growth hormone levels in the cord blood samples collected after childbirth were determined. The breastmilk was gathered within one month after childbirth for the determination of OCP levels using a high-resolution gas chromatograph with mass spectrometry, and the neurodevelopment of 10–12-month-old infants was examined using the Bayley Scales of Infant and Toddler Development(®), Third Edition (Bayley-III). It was observed that 4,4′-dichlorodiphenyl-dichloroethylene (4,4′-DDE) (mean = 10.3 ng/g lipid) was the most predominant OCP compound in the breastmilk samples. At higher concentrations (>75th percentile), specific OCPs were associated with significantly lower levels of thyroid and growth hormones than at lower concentrations (<75th percentile). Significantly higher odds ratios (ORs) were observed for binary cognitive (OR = 8.09, p = 0.025 for 4,4′-DDT), language (OR = 11.9, p = 0.013 for 4,4′-DDT) and social–emotional (OR = 6.06, p = 0.01 for trans-CHL) composite scores for specific OCPs belonging to the lower exposure group as compared to the higher OCP exposure group. The five domain Bayley-III infant neurodevelopment outcomes were negatively associated with specific OCPs in the breast milk samples based on the redundancy analysis (RDA) test. Bayley-III scales, which include cognitive, language, motor, social-emotional, and adaptive behavior scales, could be predicted by 4,4′-DDT, endrin, endosulfan I, heptachlor, or heptachlor epoxide using multivariate linear regression models with adjustment for maternal age, pre-pregnant BMI, parity, and infant gender. In conclusion, although our study showed that postnatal exposure to breast milk OCPs may be associated with infant neurodevelopmental outcomes and that prenatal exposure, if extrapolated from breastmilk levels, is associated with changes in thyroid and growth hormones that may have effects on neurodevelopment, these associations are only suggestive; thus, further studies are recommended for confirmation.